Aloe vera and wound healing: a brief review - Diaa Massoud; Barakat M. Alrashdi; Maged M. A. Fouda; Attalla El-kott; Soha A. Soliman; Hanan H. Abd-Elhafeez (Universidade de São Paulo, 2023)
Abstract Aloe vera possesses a great therapeutic importance in traditional medicine. It has attracted the attention of modern medical fields due to its wide pharmacological applications. The bioactive substances in Aloe vera proved to have antioxidant, anti-inflammatory, antibacterial, and antiviral properties. Taken into our consideration the long history of clinical applications of Aloe vera in traditional medicine, especially for promoting the healing of cutaneous wounds with rare adverse effects, it provides a cheap alternative to many expensive synthetic drugs. Recent techniques in tissue engineering created novel scaffolds based on Aloe gel extracts for wound healing applications. Nonetheless, further guided researche is required to foster the development of Aloe vera based scaffolds for the benefit of worldwide populations. Here, I systemically summarize the main events following wounding and the mechanism of action of Aloe vera in promoting the healing process. I hope to provide a solid piece of information that might be helpful for designing new research studies into this topic.